Analisis Pembiayaan Syariah Pada Bank Wakaf Mikro (BWM) Al Fithrah Wafa Mandiri Surabaya - Ghofur, Abdul; Majid Toyyibi, Abdul; Efendi, Lukman (MADINAH, 2018)
In this study, Micro Waqf Banks became the main focus because their existence was indeed a driving force for the economy of the ummah from various pre and post readiness to the process of being able to pay installments. So this research uses a descriptive qualitative type and approach by conducting field visits to meet with informants to the process of identifying field data which is carried out technically until data analysis is carried out. So that in this study the financing process was carried out in accordance with the 5C assessment and there were HALMI activities (weekly halaqoh) to build good communication between customers and BWM.